MANAJEMEN KONFLIK DALAM LEMBAGA PENDIDIKAN AGAMA ISLAM - Yustia Rachma Fitriani; Ahmad Manshur (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2025)
This study aims to analyze conflict management in Islamic educational institutions and how Islamic principles can be applied to manage emerging conflicts effectively. Conflict is a natural and unavoidable phenomenon in any organization, including Islamic educational institutions that consist of individuals with diverse backgrounds, values, and interests. This research employs a library research method, collecting data from various books, journals, and relevant academic sources. The results indicate that conflicts in Islamic educational institutions may arise from differences in perspectives, leadership styles, ineffective communication, and limited resources. Therefore, it is essential to implement conflict management strategies based on Islamic values such as syura (consultation), ‘adl (justice), islah (reconciliation), ihsan (benevolence), and ukhuwah islamiyah (brotherhood). By applying these principles, conflicts can be transformed into opportunities for learning, strengthening social relations, and improving institutional quality. In conclusion, effective and Islamic-based conflict management can foster a harmonious, conducive, and productive environment within Islamic educational institutions.